The Implementation of a Primary Care-Based Integrated Mobile Health Intervention for Stroke Management in Rural China: Mixed-Methods Process Evaluation - Gong, Enying; Sun, Lixin; Long, Qian; Xu, Hanzhang; Gu, Wanbing; Bettger, Janet Prvu; Tan, Jingru; Ma, Jixiang; Jafar, Tazeen Hasan; Oldenburg, Brian; Yan, Lijing L. (Frontiers in Public Health, 2021)
Background: There is a lack of evidence concerning the effective implementation of strategies for stroke prevention and management, particularly in resource-limited settings. A primary-care based integrated mobile health intervention (SINEMA intervention) has been implemented in rural China to improve the health of community-dwelling stroke survivors. The program was evaluated with a one-year-long cluster-randomized controlled trial. This paper reports the findings from the trial implementation evaluation and identifies factors that may influence the wider implementation of SINEMA in the future. Methods: We developed an evaluation framework by employing both the RE-AIM framework and the MRC process evaluation framework to describe the implementation indicators, related enablers and barriers, and illustrate some potential impact pathways that may influence the effectiveness of the intervention in the trial. The research team used data collected from participants as well as from the digital health monitoring systems. In addition, we conducted quarterly in-depth interviews with stakeholders in order to understand barriers and enablers of program implementation and effectiveness. Quantitative data analysis and thematic qualitative data analysis were applied, and the findings were synthesized based on the evaluation framework. Results: The SINEMA intervention was successfully implemented in 25 rural villages and reached 637 stroke patients in rural Northern China during the 12 months of the trial. Almost 90% of participants received all follow-up visits, and about half of the participants received daily voice messages. The majority of the intervention components were adopted by village doctors, although with some adaptation. The coherence of the intervention component enabled the implementation and the interaction between human-delivered and technology-enabled components reinforced the program effectiveness. However, participants’ characteristics, doctor-patient relationships and the healthcare system context attributed to the variation of program implementation and effectiveness. Conclusion: A comprehensive evaluation of program implementation demonstrates that the SINEMA program was well-implemented in rural China. Findings from this research provide additional information for program adaptation. Further research is needed to investigate how the SINEMA program could be more widely implemented in resource-limited settings.